2014
DOI: 10.1038/npp.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Subanesthetic Ketamine Treatment Promotes Abnormal Interactions between Neural Subsystems and Alters the Properties of Functional Brain Networks

Abstract: Acute treatment with subanesthetic ketamine, a non-competitive N-methyl-D-aspartic acid (NMDA) receptor antagonist, is widely utilized as a translational model for schizophrenia. However, how acute NMDA receptor blockade impacts on brain functioning at a systems level, to elicit translationally relevant symptomatology and behavioral deficits, has not yet been determined. Here, for the first time, we apply established and recently validated topological measures from network science to brain imaging data gained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 71 publications
(96 reference statements)
6
37
1
Order By: Relevance
“…Our analysis of these acute effects of ketamine may be a more appropriate analogy of the prodromal phase of schizophrenia (Honey et al, 2008) rather than later, at disease manifestation. This is consistent with recent imaging studies in rodents, which also suggest aspects of frontal hyperconnectivity following acute ketamine (Gass et al, 2014;Dawson et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Our analysis of these acute effects of ketamine may be a more appropriate analogy of the prodromal phase of schizophrenia (Honey et al, 2008) rather than later, at disease manifestation. This is consistent with recent imaging studies in rodents, which also suggest aspects of frontal hyperconnectivity following acute ketamine (Gass et al, 2014;Dawson et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The effect of ketamine on LPFC neurons may have its origins within the LPFC itself or may be a secondary effect of changes in the firing of neurons in afferent regions. In support of this latter possibility, acute ketamine administration has been reported to cause hyperconnectivity between the PFC and other cortical and thalamic regions (Dawson et al, 2013(Dawson et al, , 2014Anticevic et al, 2015b). Such hyperconnectivity was also observed in patients with early-stage schizophrenia (Anticevic et al, 2015a,b).…”
Section: Discussionmentioning
confidence: 88%
“…NMDA receptor function (D'Souza et al, 2012) may be necessary to restore both the strength and the consistency in working memory representation in the LPFC.…”
mentioning
confidence: 99%
“…NMDA antagonists increase the levels of excitatory neurotransmitters, such as glutamate, acetylcholine, and histamine and disinhibit GABAergic interneurons (Olney and Farber 1995). In a recent study, mice treated with a high dose of ketamine (30 mg/kg) showed a global increase in graphtheory-based connectivity measures (degree and mean clustering coefficient), as well as an increase in thalamo-cortical and cortical-subcortical (PFC to dorsal raphe nuclei and locus coeruleus) connectivity (Dawson et al 2014). In this study, the authors did not provide specific data on PFC-HC coupling.…”
Section: Discussionmentioning
confidence: 99%